Orígenes y evolución del Tratado de Libre Comercio del G-3: una mirada hacia el regionalismo en América Latina - Ortiz-Mena López-Negrete, Antonio (Revista Mexicana de Política Exterior, 2022)
In this article, the author analyzes the origins and evolution of the G-3 Free Trade Agreement, with a view to helping us come to a better understanding of this particular integration process. Specifically, the objective of this study is to elucidate the reasons that led to the creation of the G-3 FTA, and to determine if its evolution has lived up to the expectations that gave rise to it. We are provided with the hypotheses of several experts on the causes, origins and dynamics of regionalism, including explanations of strategic interaction, empirical aspects of integration, economic interdependence and the internal economic and political motivations that may emerge in a given country. Ortiz examines the development of trade and investment relations between G-3 FTA member countries from 1995 to date and their implications for Mexico, and rounds up by pointing out some of the challenges G-3 FTA member countries currently face.